A rare clinical presentation of Waldenström Macroglobulinemia mimicking lung cancer. (2022) - Laursen, Michael RT.; Kolekar, Shailesh; Sivapalan, Pradeesh; Clementsen, Paul F.; Bodtger, Uffe
Abstract: Waldenström macroglobulinemia rarely presents as pulmonary symptoms, and even rarer as chylothorax. We present a patient who presented with bilateral pleural effusion and a 30 mm solid lesion in the lung. Biochemical analysis of the pleural fluid revealed chylothorax. The 18-fluorodeoxygenase positron emission tomography, bronchoscopy, endobronchial ultrasound, and cytological examination of the pleural fluid, showed no apparent cause of the chylothorax. The diagnostic breakthrough was made with flow cytometry of the pleural fluid, which revealed a small group of clonal B-cells. Biopsy from the parietal pleura and bone marrow led to the diagnosis Waldenström macroglobulinemia. This demonstrates that flow cytometry should be considered when routine diagnostics do not lead to a reach a specific diagnosis.